2020
DOI: 10.1016/j.tig.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Chromatin Imaging at Kilobase-Scale Resolution

Abstract: HighlightsMicroscopy now allows the measurement of the polymeric structure of chromatin in intact, fixed nuclei, with a resolution of a few kilobases.Multiway contact interactions and physical separation of domains can be probed directly.Structural information can be combined with measurements of nascent transcription, nuclear position, cellular position, and cellular morphology.Single-cell imaging validates many of the features previously identified by bulk, proximity-based approaches, and challenges existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 177 publications
(287 reference statements)
1
85
0
3
Order By: Relevance
“…Moreover, HiC identified functional sequence elements, e.g., CTCF, involved in the maintenance of genome folding (Dixon et al 2012 ; Nuebler et al 2018 ). Optical and electron microscopy revealed that chromatin density distribution inside human nuclei is quite heterogeneous (Ou et al 2017 ; Boettiger and Murphy 2020 ; Boopathi et al 2020 ) with major chromatin compartments being euchromatin and heterochromatin (Solovei et al 2016 ; Bonev and Cavalli 2016 ; Van Steensel and Belmont 2017 ). The former represents loosely packed transcriptionally active chromatin, whereas the latter corresponds to more condensed chromatin that houses predominantly silenced genes.…”
Section: Nuclear Organization and Heterogeneitymentioning
confidence: 99%
“…Moreover, HiC identified functional sequence elements, e.g., CTCF, involved in the maintenance of genome folding (Dixon et al 2012 ; Nuebler et al 2018 ). Optical and electron microscopy revealed that chromatin density distribution inside human nuclei is quite heterogeneous (Ou et al 2017 ; Boettiger and Murphy 2020 ; Boopathi et al 2020 ) with major chromatin compartments being euchromatin and heterochromatin (Solovei et al 2016 ; Bonev and Cavalli 2016 ; Van Steensel and Belmont 2017 ). The former represents loosely packed transcriptionally active chromatin, whereas the latter corresponds to more condensed chromatin that houses predominantly silenced genes.…”
Section: Nuclear Organization and Heterogeneitymentioning
confidence: 99%
“…This dynamics-based perspective can be used to amend the conventional perspective of the 3D genome organization. Recent advances in super-resolution chromatin imaging of fixed cells have revealed the physical 3D conformations of labeled chromatin domains in a few hundred kb sizes [53] , [54] . Furthermore, super-resolution chromatin tracing reveals TAD-like structures, which are separated globules in single cells, and the sum of the contacts in the 3D conformations is consistent with population-averaged Hi-C data [55] , [56] .…”
Section: Emergence Of Chromatin Domains In Systems With Dynamic Fluctmentioning
confidence: 99%
“…Although TADs have often been depicted as distinct, separate globules in schematic figures ( Fig. 6A ), it is unclear what is a structural feature of TADs in microscope observations [54] . Interestingly, the snapshots by cryo-electron microscopy (EM) [57] , [58] and EM tomography [59] techniques reveal not distinct chromatin globules but rather irregularly folded chromatin fibers.…”
Section: Emergence Of Chromatin Domains In Systems With Dynamic Fluctmentioning
confidence: 99%
“…However, all sequencing-based methods are by nature invasive and thus make microscopy-based single-cell time course experiments a necessity to understand the dynamic behavior of chromatin. For a comprehensive comparison between different imaging techniques used to studying genome organization and transcription, we refer the reader to recent reviews [8][9][10][11]. In addition, imaging techniques can be multiplexed for simultaneous visualization of a multitude of chromatin constituents and are amenable to highthroughput analysis of genome organization at kilobase resolution [10].…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive comparison between different imaging techniques used to studying genome organization and transcription, we refer the reader to recent reviews [8][9][10][11]. In addition, imaging techniques can be multiplexed for simultaneous visualization of a multitude of chromatin constituents and are amenable to highthroughput analysis of genome organization at kilobase resolution [10]. While super resolution imaging-based approaches are often performed in fixed cells, time-resolved wholechromatin imaging recently revealed that chromatin moves in a spatially and temporally correlated manner at a nanoscale resolution [12,13].…”
Section: Introductionmentioning
confidence: 99%